Analytical solutions of katabatic wind at Mizuho and Syowa Station, Antarctica - Adachi, Takashi (1984)
P(論文) A new analytical solution of governing equations for stationary katabatic winds is derived under the assumptions that the two horizontal orthogonal components of geostrophic winds vary linearly with height and the effect of the cold sloping surface decreases exponentially with increasing height. Eddy diffusivity is assumed constant. Calculated wind profiles agree well with observations at Mizuho and Syowa Stations, Antarctica except in the surface layer. departmental bulletin paper